2010
DOI: 10.1021/jp102446w
|View full text |Cite
|
Sign up to set email alerts
|

Study of Heterogeneous Electron Transfer on the Graphene/Self-Assembled Monolayer Modified Gold Electrode by Electrochemical Approaches

Abstract: The electrochemical behaviors of graphene sheets attached to a self-assembled monolayer (SAM) on a gold electrode have been investigated. A gold electrode is sequentially modified by the SAM of n-octadecyl mercaptan (C 18 H 37 SH), followed by controllable adsorption of graphene sheets to obtain a graphene/SAM modified Au electrode. The graphene/SAM modified Au electrode is characterized electrochemically by using ruthenium hexaammine (Ru(NH 3 ) 6 3+) as a redox probe, and by atomic force microscopy (AFM) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 74 publications
(76 reference statements)
1
39
0
Order By: Relevance
“…The corresponding apparent heterogeneous electron‐transfer rate constants have been also estimated at 100 mV/s, as scan rate, by CV, according to our previous work . The kinetic results , are highlighted on Table , where it is possible to recognize the highest value of the heterogeneous apparent electron‐transfer kinetic constant in presence of FB‐SPE devices. This means that the FB‐SPE sensor catalyzes the redox reversible electron‐transfer reaction of hexaammineruthenium (III) chloride, better than the others modified electrodes (as shown on Figure S2 and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding apparent heterogeneous electron‐transfer rate constants have been also estimated at 100 mV/s, as scan rate, by CV, according to our previous work . The kinetic results , are highlighted on Table , where it is possible to recognize the highest value of the heterogeneous apparent electron‐transfer kinetic constant in presence of FB‐SPE devices. This means that the FB‐SPE sensor catalyzes the redox reversible electron‐transfer reaction of hexaammineruthenium (III) chloride, better than the others modified electrodes (as shown on Figure S2 and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Xie et al used graphene nanosheets prepared by arc-discharge method to modify n-octadecyl mercaptan self-assembled monolayer (SAM) on a gold electrode. The Au electrode was firstly deactivated by SAM deposition, however, upon placement of the graphene nanosheets on the SAM, the electron transfer was restored as confirmed using CV and scanning electrochemical microscopy (SECM) with Ru(NH 3 ) 6 3+/2+ mediator [109]. Questions remain as to whether the restored electroactivity originates from incorporation of graphene into the SAM or a physical contact between the nanosheets and Au surface.…”
Section: Iinear Diffusionmentioning
confidence: 98%
“…Xie et al investigated the electrochemical behaviors of graphene sheets attached to a SAM (n-octadecyl mercaptan) on a gold electrode (Figure 25). Their studies revealed that the heterogeneous electron transfer blocked by the SAM layer can be restored by graphene sheets, and the graphene-/SAM-modified Au electrode had a smaller interfacial capacitance, as compared with that of a bare one [69].…”
Section: Graphene Synthesis By Sammentioning
confidence: 99%